The utility of ultrasound to predict the uncuffed endotracheal tube size in pediatric population - Reena Pal; Jerry Joseph Joel; Anity Singh; Rachel Gandi; Ekta Rai (CHRISMED Journal of Health and Research, 2021)
Introduction: Due to contrasting evidence for and against the age-based formulas for calculation of correct size of endotracheal tube (ETT) in children, this prospective observational study aimed at comparison of ultrasonography (USG) and age-based formula for calculation of correct ETT size in children <6 years of age. Materials and Methods: Following a sample size calculation of 63 children, children of <6 years of age were recruited. Age-based formula (Cole's formula) was used for predicting ETT size. Cricoid diameter was measured using USG, and USG ETT was selected. Correct tube used for the patient was confirmed by air leak test. Agreement for correct size ETT with USG and age-based method was assessed using kappa value for intraclass correlation (ICC). Subgroup analysis was carried out for age, sex, and weight. Results: Sixty-six children with a mean age of 27.9 months were recruited. USG method was found to be correct in 44 patients (67%), whereas age-based method selected the correct tracheal tube size in 32% (21) of patients (P < 0.001). Agreement of ultrasound-based method with the correct size tube was 0.902, while the same for age-based formula method and correct ETT was 0.835 proving the superiority of the USG. On subgroup analysis, ultrasound-based tube selection was accurate in children <1 year. Conclusions: With ICC of 0.902, ultrasound can be a useful tool for selecting pediatric ETT size as compared to age-based formula. This finding is significant, especially in children under the age of 1 year.